Optimizing Chronotherapy in Psychiatric Care: The Impact of Circadian Rhythms on Medication Timing and Efficacy - Cezar-Ivan Colita; Dirk M. Hermann; Madalina Filfan; Daniela Colita; Thorsten R. Doepnner; Oana Tica; Daniela Glavan; Aurel Popa-Wagner (Clocks & Sleep)
In many medical settings, medications are typically administered in the morning or evening, aligning with patients’ daily routines. This practice does not stem from chronotherapy, which involves scheduling drug administration to enhance its effectiveness, but rather from the way clinical operations are structured. The timing of drug administration can significantly affect a medication’s effectiveness and side effects, with the impact varying by up to ten times based on circadian rhythms. Disorders such as major depression, bipolar disorder, and schizophrenia are linked to disruptions in these rhythms. Recent studies have found that circadian dysfunctions, including genetic and neurohumoral changes, underlie many psychiatric conditions. Issues such as an altered glucocorticoid rhythm due to impaired HPA axis function, disturbed melatonin balance, and sleep disturbances have been noted in psychotic disorders. Furthermore, mood disorders have been associated with changes in the expression of circadian rhythm genes such as Clock, Bmal1, and Per. Considering that the absorption, biodistribution, effects on target organs, half-life, metabolism, and elimination of drugs are all influenced by the body’s circadian rhythms, this narrative review explores the optimal timing of medication administration to maximize efficacy and minimize side effects in the treatment of psychiatric disorders. By closely monitoring circadian variations in cortisol, melatonin, and key clock genes, as well as by deepening our understanding of the metabolisms and pharmacokinetics of antipsychotic medications, we propose a chronotherapy approach for psychiatric patients that could significantly enhance patient care.